2021
DOI: 10.1186/s12917-021-02774-4
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity study of a Streptococcus suis autogenous vaccine in preparturient sows and evaluation of passive maternal immunity in piglets

Abstract: Background Streptococcus suis is an important pathogen that causes severe diseases mostly in weaned piglets. Only available vaccines in the field are those composed of killed bacteria (bacterins) but data about their effectiveness are missing. We report here a field study on the immunological response induced by an autogenous vaccine applied in pre-parturient sows. Using a farm with recurrent S. suis serotype 7 problems, the study was divided in three experiments: (I) Sows received the vaccine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 26 publications
2
15
1
Order By: Relevance
“…Vaccine interference with maternal antibodies has specifically been suggested for S. suis [ 23 ]. As previously reported, piglets used in the current study possessed maternal antibodies, since most sows are colonized by S. suis (or S. suis -like microorganisms) and normally possess high levels of antibodies [ 13 , 23 , 25 ]. High basal levels of maternal antibodies reacting with whole bacteria of S. suis serotype 2 were still present at weaning, which might explain the fact that one-dose immunization was not sufficient to induce a significant increase in specific anti- S. suis antibodies in vaccinated piglets and this independently of the adjuvant used.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Vaccine interference with maternal antibodies has specifically been suggested for S. suis [ 23 ]. As previously reported, piglets used in the current study possessed maternal antibodies, since most sows are colonized by S. suis (or S. suis -like microorganisms) and normally possess high levels of antibodies [ 13 , 23 , 25 ]. High basal levels of maternal antibodies reacting with whole bacteria of S. suis serotype 2 were still present at weaning, which might explain the fact that one-dose immunization was not sufficient to induce a significant increase in specific anti- S. suis antibodies in vaccinated piglets and this independently of the adjuvant used.…”
Section: Discussionmentioning
confidence: 78%
“…These antibodies might have been generated in adult animals by S. suis strains that are part of the normal microbiota or even by other S. suis -like microorganisms that are present in the upper respiratory tract [ 3 , 24 ]. Adult animals usually present high levels of antibodies tested for any serotype of S. suis [ 13 , 25 ] (unpublished observations), which may explain why S. suis -associated diseases are almost never observed in older animals [ 10 ]. Finally, in addition to the presence of some residual maternal antibody interference, other features that might also explain the lack of immunological response after one vaccine dose include an immature immune system, diet change, and other stressing factors [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Absence of protective responses from these vaccines have been attributed to the failure of whole-bacterial antigens to elicit an immune response due the inactivation processing, production of antibodies to antigens not associated with protection, and/or the use of inappropriate adjuvants [ 6 , 11 , 16 ]. Indeed, it is difficult to compare published studies with different autogenous vaccines [ 12 – 14 ], as they may use different adjuvants, bacterial concentrations as well as conditions used to make the pathogen grow and bacterial killing methods, among other variables. In addition, no field studies have evaluated the usefulness of an autogenous vaccine in the complete absence of antimicrobials on the farm.…”
Section: Introductionmentioning
confidence: 99%
“…However, published studies on the use of autogenous vaccines in the field showed so far limited and/or no increase of passive maternal antibodies in piglets during the nursery barn period [ 11 13 ]. Two of these published field studies used vaccines manufactured within the same commercial vaccine company [ 12 , 13 ]. Further research on length and duration of passive maternal immunity elicited by vaccines produced by different manufacturing companies is required.…”
Section: Introductionmentioning
confidence: 99%
“…A glycoconjugate vaccine candidate against S. suis serotype 2 (SS2) based on isolated CPS and semisynthetic glycoconjugate vaccine candidates for SS2, SS3, SS9, and SS14 have been evaluated. , The S. suis serotype 18 CPS pentasaccharide repeating unit provides an interesting challenge for synthetic chemists as a first step toward a glycoconjugate vaccine for this serotype. The SS18 pentasaccharide repeating unit made up of [→3)- d -GalNAc­(α1-3)­[ d -Glc-(β1-2)] d -GalA4OAc­(β1-3)- d -GalNAc­(α1-3)- d -BacNAc4NAc­(α1→] n (Figure a) requires the installation of a 1,2- cis linkage between d -bacillosamine and the reducing-end linker. The central galacturonic acid branching unit is a challenge concerning the poor reactivity and protecting group orthogonality.…”
mentioning
confidence: 99%